PERAN PENGAWAS DALAM MENINGKATKAN KINERJA KEPALA SEKOLAH DI ERA MERDEKA BELAJAR: Penelitian Kualitatif - Ana Supriati; Sudadi; Zulfah; Soedjono (STKIP Subang, 2024)
In the era of independent leaning, the quality of education is still a major problem. Efforts to change were made by the Ministry of Education, Culture, Research and Technology. The fundamental change is that there is a change in the curriculum. Improving teacher competence is carried out through various training models. The principal as the manager of the educational unit is improved. Changes in the role of the supervisor are carried out. One of the roles of the supervisor is to provide assistance to educational units. Through assistance activities, supervisors are expected to be able to empower the head of the educational unit. Supervisors can supervise and monitor the performance of the principal. This study aims to determine whether there is a role for supervisors in improving the performance of the principal of Al Yakin Yunior High school. This study is qualitative. The researcher's framework argues that with a well-planned assistance process, the performance of the principal can be improved. Data collection carried out by the researcher: interviews, observations, and documentation. Through the triangulation process, the researcher obtained valid research results. From the data obtained from various sources, the researcher describes the results of his research. The principal can involve teachers and education personnel. The principal in managing the educational unit needs the support of a work team consisting of the vice principal, teachers and education personnel. With the assistance of the supervisor and the active role of teachers and education personnel, the principal can manage the school effectively.